Analysis of Mass Media Development in Public Relations at CNN Company - Praditia, Ariya (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
In the digital and globalization era, the development of information technology affects almost all aspects of life, including a company's Public Relations (PR) strategy. Digital mass media has become an important tool for delivering information to audiences quickly and efficiently, allowing for interaction without geographical limitations. CNN (Cable News Network), founded in 1980, has undergone a significant transformation in how it communicates with its audience. This study aims to analyze the development of PR mass media at CNN, evaluate the effectiveness of their PR strategies in enhancing audience engagement, and maintaining credibility amidst digital challenges. By leveraging social media for two-way communication, CNN can gather feedback, respond to issues promptly, and increase engagement through interactive content. However, challenges such as misinformation and changing audience preferences remain. This study finds that the use of big data to analyze audience behavior and multimedia content innovation is key to maintaining audience attraction and loyalty. Additionally, CNN's PR must navigate complex relationships with various stakeholders while preserving journalistic integrity. The results of this research are expected to provide valuable insights for the development of more effective PR strategies in the mass media industry, with a focus on data-driven principles and content innovation. Keywords: Public Relations, CNN, mass media, digital technology, disinformation, big data, content innovation, audience engagement, credibility, stakeholders.